Effect of fluid ingestion on neuromuscular function during prolonged cycling exercise. Issue 4 (25th March 2005) - Vallier, J-M; Grego, F; Basset, F; Lepers, R; Bernard, T; Brisswalter, J
Abstract : Objectives: To investigate the effects of fluid ingestion on neuromuscular function during prolonged cycling exercise. Methods: Eight well trained subjects exercised for 180 minutes in a moderate environment at a workload requiring ∼60% maximal oxygen uptake. Two conditions, fluid (F) and no fluid (NF) ingestion, were investigated. Results: During maximal voluntary isometric contraction (MVC), prolonged cycling exercise reduced (p<0.05) the maximal force generating capacity of quadriceps muscles (after three hours of cycling) and root mean square (RMS) values (after two hours of cycling) with no difference between the two conditions despite greater body weight loss (p<0.05) in NF. The mean power frequency (MPF) for vastus lateralis muscle was reduced (p<0.05) and the rate of force development (RFD) was increased (p<0.05) only during NF. During cycling exercise, integrated electromyographic activity and perceived exertion were increased in both conditions (p<0.05) with no significant effect of fluid ingestion. Conclusions: The results suggest that fluid ingestion did not prevent the previously reported decrease in maximal force with exercise duration, but seems to have a positive effect on some indicators of neuromuscular fatigue such as mean power frequency and rate of force development during maximal voluntary contraction. Further investigations are needed to assess the effect of change in hydration on neural mechanisms linked to the development of muscular fatigue during prolonged exercise.